Tari Baris Gede Télék at Pura Dalem Kedewatan Desa Adat Sanur: A Study of Form and Function - Anak Agung Made Anom Wira Kusuma; M. Jazuli; Widodo - (Institut Seni Indonesia Denpasar, 2023)
The people of Sanur Traditional Village preserve culture through a process of solidarity, meaning the process between the dance performance of Baris Gede Télék as a local art entity and the local community as its supporters who are faced with something sublimation. The sublimation in question is a process of adjusting society to the development of newer times, but not abandoning existing art. The focus of this research is the form and function of Baris Gede Télék dance. The purpose of this research is to increase understanding and awareness of Balinese art, especially in Baris Gede Télék dance in life, which will basically always exist and remain sustainable. The method used as the basis for the analysis stage is a qualitative method that is descriptive-analytical by identifying and describing a phenomenon that occurs in the field as it is. The sources presented in this paper are obtained from direct observation, then an interview was conducted with the relevant informant, and deepened by the study of documents obtained from a collection of archives, books, videos, and audio recordings related to Baris Télék dance. The collected data is then analyzed through the stages of data reduction, data presentation, and data verification before the data is concluded. With the application in the cultural inheritance space, the people of Sanur Traditional Village are expected to be able to be faced with a process of educating the self-awareness of the community as cultural supporters in the context of directing art, so as to form a character value that will have a major influence on the development of the local community.